2004
DOI: 10.1097/00001756-200403010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Fractionating language comprehension via frequency characteristics of the human EEG

Abstract: We present a new analysis technique for EEG research on language comprehension, which dissociates superficially indistinguishable event-related potential (ERP) components. A frequency-based analysis differentiated between two apparently identical but functionally distinct N400 effects in terms of activity in separable frequency bands, and whether the activity stemmed from increased power or phase locking. Whereas linguistic problem detection is associated with theta band activity (approximately 3.5-7.5 Hz), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 18 publications
5
64
0
1
Order By: Relevance
“…Thus, the detailed analysis of oscillatory activity may allow for differentiating EEG effects that appear indistinguishable in the ERP. Consistently, Roehm, Schlesewsky, Bornkessel, Frisch, and Haider (2004) recently showed that two similar ERP waveforms may differ with respect to phase locking and power; they found the ERP of one experimental condition to be accompanied by large power and weak phase locking, and found the ERP of the other experimental condition to be accompanied by low power and large phase locking.…”
Section: Erp Correlates Of Recognition Memorymentioning
confidence: 57%
“…Thus, the detailed analysis of oscillatory activity may allow for differentiating EEG effects that appear indistinguishable in the ERP. Consistently, Roehm, Schlesewsky, Bornkessel, Frisch, and Haider (2004) recently showed that two similar ERP waveforms may differ with respect to phase locking and power; they found the ERP of one experimental condition to be accompanied by large power and weak phase locking, and found the ERP of the other experimental condition to be accompanied by low power and large phase locking.…”
Section: Erp Correlates Of Recognition Memorymentioning
confidence: 57%
“…A previous study using oscillatory analysis in language comprehension paradigms has reported that grammatical violations lead to a higher degree of stimulus-evoked activity in the lower theta band than the grammatical conditions [Roehm et al, 2004]. This study claimed that an irresolvable conflict in language processing produces a reorganization in the sense of phase resetting.…”
Section: Spectral Power Analysis: Low Frequency Responsementioning
confidence: 79%
“…Rugg & Coles, 1995). Different occurrences of a component that differ only with regard to amplitude or latency are consistent with quantitative variations in the underlying process, though they do not unequivocally call for a quantitative explanation as there is a many-to-one mapping between cognitive subdomains and individual ERP components (e.g., Roehm, Schlesewsky, Bornkessel, Frisch, & Haider, 2004). Hence, previous ERP findings on the reanalysis of case ambiguities in German accusative sentences clearly established that different structures induce different degrees of processing cost.…”
Section: Detecting Qualitative Distinctions In Reanalysismentioning
confidence: 91%